THE VALUES AND (INTER) CULTURAL PRACTICES OF STUDENTS IN FRANCE AND ARMENIA - Derhy Kurtz , B. W. L.; Basco , L. (Արդի հոգեբանություն, 2021)
The article presents the continuation of joint research projects initiated, as a result of which it be-came possible to study the differences in the perception of the student audience, which are located, on the one hand, in France, and on the other hand, in Armenia. This made it possible to identify connections and interactions between the personal values of students and their practice. Spiritual or religious values, family values, artistic values, values associated with pleasure and / or self-realization, values associated with freedom and values associated with new technologies were especially studied. This stage of the study made it possible to establish in what forms and under what conditions the connections of values and (inter) cultural practices are manifested. With regard to intercultural interaction and exchange between the two countries, it was possible to describe, explain and measure how the gaps in the perception of the student image representations as a person in France and in Armenia could be noted.